UTILIZATION OF FINANCIAL TECHNOLOGY IN THE LIFE OF THE TEMBILAHAN COMMUNITY - Yopi Mayendra Pratama S; Junita ahira Putri (Indragiri Research Center (ingreat), 2025)
The development of digital technology has brought changes to the financial system, one of which is the emergence of Financial Technology (FinTech). Financial technology offers convenience, speed, and efficiency in conducting financial transactions. This journal article aims to examine the use of Financial Technology in the lives of the Tembilahan community and the benefits experienced by the community. The method used in this article is a descriptive method with a literature study approach, namely reviewing books, journals, and articles relevant to the topic of Financial Technology. The results of the study indicate that the use of Financial Technology such as e-wallets, mobile banking, and QRIS provides benefits in the form of ease of transactions, time efficiency, and increased access to financial services. These benefits have impacted the financial activities of the Tembilahan community in their daily lives.